Fatores de risco e epidemiologia dos distúrbios da comunicação em crianças de cinco anos de idade da coorte de nascimento de 2005 em Aracaju-SE - Sales, Neuza Josina (2013)
Children Communication Disorders (CCD) are correlated to multifactorial causes, which interfere on the children´s interaction with the environment. Objectives: To study the relationship between biological, socio demographic and economic, interactional-affective and functional factors with the CCD: speech, voice, orofacial motricity and stomatognathic functions; to determine the prevalence and identify CCD risk and protection factors at five years of age. Method: a cross-sectional study with children belonging to the 2005 live birth cohort from Aracaju-SE. Data collection was done at 141 public and private institutions within Aracaju districts, after taking written authorization from relatives responsible for the children. Validated protocols were used to speech analysis (TERDAF) and orofacial motricity and stomatognathic functions (AMIOFE). The visual-analogical scale (CAPE-V) scores measured voice deviant general level (GGDVDM). Expert speech-language pathologist interviewed the responsible for the children and evaluated them. Univariated and multivariated data analysis were used. Results: 371 children were studied, from both sex and age average of 5.12 years old. Regarding biological factors, 108 (29%) children were born by cesarean sections. Anthropometric measures were taken at birth and 17 (4%) children were low weight. Regarding socio-demographic-economic factors, 126 (34.5%) lived on north area receiving up to three minimum wages as familiar income. Concerning interactional-affective factors, only 23 (6%) mothers take direct care of their children, 338 (91%) children were breast fed, being 244 (66%) longer than three months and 207 (56%) children were cared by employed caregivers. Regarding functional factors, 173 (48%) children said their first words before one year old and 197 (52%) between one and two years of age; 229 (62%) were restless; 110 (30%) presented attention difficulties and 46 (12%) depended on their caregivers to their everyday activities. During sleeping 124 (34%) children were restless, 135 (37%) presented sialorrhea and 114 (31%) snored. The prevalence of CCD was 76.5%, being 65.8% presenting phonological disorder (PD), 26.4% presenting discreet to moderate voice deviant general level (GGDVDM) and 15.4% with mild orofacial motricity dysfunction (DMO). Sixteen phonological processes (PP) of moderated severity were identified and were not expected for this age. The DMO average score was lower on subjects born by cesarean section, presenting inappropriate weight and with relation to the marital situation. The GGDVDM was higher in 47 (34%) children with preponderant quiet temper. The DMO and the GGDVDM showed some difference regarding familiar income. On the multivariated analysis, the protective factor of children´s communication was normal childbirth. The risk factor was preponderant quiet temper and more than four dwellings at residence. Conclusion: there was high prevalence of CCD related to speech, voice and orofacial motricity, with multifactorial etiology. Normal delivery (biological variable) was a protective factor, and the socio-demographic-economic factors such as more than four persons per house and preponderant quiet temper represent greater risk. Surveillance multidisciplinary intervention actions directed to the children and their families may minimize social educational difficulties and promote well-being and quality life in different life periods.